AMINOACIDURIA AND MEGALOBLASTIC ANAEMIA. Issue 3 (May 1960) - Fowler, D.; Cox, E. V.; Cooke, W. T.; Meynell, M. J.
Abstract : Urinary amino-acid chromatograms from 23 patients with megaloblastic anaemia have been studied before and after therapy. The most consistent abnormality was an increased taurine or increased taurine/glycine ratio. This was not related directly to deficiency of vitamin B12 or folic acid or to the degree of anaemia.